2011
DOI: 10.1889/jsid19.12.888
|View full text |Cite
|
Sign up to set email alerts
|

A study on overhead glare in office lighting conditions

Abstract: Abstract— High‐intensity light sources illuminating the human eye may create discomfort glare, or at higher intensities even disability glare. In many office lighting conditions, light from overhead luminaires in the ceiling may deliver stray light into human eyes, and as such create discomfort glare, generally referred to as overhead glare. In this paper, overhead glare for a LED luminaire comprising a matrix array of small LED sources using subjective evaluation methodologies and theoretical models, commonly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…The glare rating was used as dependent variable, the luminance level (5 levels) as fixed factor, and the subjects as random factor. As could be expected from existing literature [2, [4][5]7], the result showed a statistically significant effect of luminance level on perceived discomfort glare (p<0.001). The perceived glare logarithmically increased with the luminance (r2=0.99), as shown in Fig.1.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The glare rating was used as dependent variable, the luminance level (5 levels) as fixed factor, and the subjects as random factor. As could be expected from existing literature [2, [4][5]7], the result showed a statistically significant effect of luminance level on perceived discomfort glare (p<0.001). The perceived glare logarithmically increased with the luminance (r2=0.99), as shown in Fig.1.…”
Section: Resultssupporting
confidence: 87%
“…The LED luminaires used were specifically built by Philips Lighting, and were also used in the research by Xia et al [7]; they consisted of a 7x7 array of LEDs, but contrary to their previous use the LEDs now were covered with diffusers with 90% light transmissivity. The average luminance of the exit window was controlled by a Dali (Digital Addressable Lighting interface) controller between 1148 cd/m2 and 4842 cd/m2.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Geerdinck et al 43 found, based on acceptance scores, that luminaires with non-uniform luminance patterns provoke more discomfort glare than uniform light sources in office landscapes. Xia et al 50 agreed with Geerdinck et al 43 and highlighted, based on their repeated measures design, that the luminance level of the exit window of the LED luminaire has a significant effect on perceived overhead glare. Hirning et al 48 investigated discomfort glare in a field study.…”
Section: Glarementioning
confidence: 65%
“…However, as with any new technology, it can have some unwanted properties that were absent or less dominant for the conventional, wellestablished, lighting technologies. In particular, the high intensity of individual LEDs and their non-uniform luminance distribution in a luminaire can give rise to discomfort glare, which eventually could induce serious visual fatigue [1]. The widely used Unified Glare Rating [2] does not always correctly predict the degree of experienced discomfort glare for these particular LED-based luminaires.…”
Section: Introductionmentioning
confidence: 99%